1992
DOI: 10.1007/bf01261455
|View full text |Cite
|
Sign up to set email alerts
|

Leaf surface compound fromBrassica oleracea (Cruciferae) induces oviposition byPieris brassicae (Lepidoptera: Pieridae)

Abstract: SummaryChemicals present on the surface of cabbage (Brassica oleracea L.) leaves were extracted by dipping these leaves for 3 s in dichloromethane followed by a 3 s dip in methanol. When offered in dual choice bioassays using green paper cards as a substrate, the methanol extract stimulated oviposition activity by Pieris brassieae L. (Lepidoptera: Pieridae) females. The oviposition stimulant was isolated using medium pressure liquid chromatography, reversed-phase HPLC, ion-pair HPLC and ion exchange chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 33 publications
(38 reference statements)
1
80
1
2
Order By: Relevance
“…Glucosinolates can act as feeding stimulants and oviposition stimulants on a range of insect species (Louda and Mole, 1991;van Loon et al, 1992). For example, caterpillars of cabbage white butterflies (Pieris spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Glucosinolates can act as feeding stimulants and oviposition stimulants on a range of insect species (Louda and Mole, 1991;van Loon et al, 1992). For example, caterpillars of cabbage white butterflies (Pieris spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Oviposition-deterring pheromones are natural and species-specific compounds that inhibit oviposition, and seem suitable chemicals to reduce crop infestation by insects utilising them, since they produce very low environmental risks (Schoonhoven, 1990). The potential of glucosinolates in stimulating feeding by larvae and oviposition by adults has been confirmed for P. brassicae and P. rapae through studies showing that ovipositing P. rapae adults respond more strongly to indole glucosinolates, such as glucobrassicin, and less strongly to aliphatic glucosinolates, such as glucocheirolin (Rodman and Chew, 1980;Renwick et al, 1992;Van Loon et al, 1992;Huang and Renwick, 1993;Renwick, 2001). Some of these studies showing response of these insects towards glucosinolates and isothiocyanates are described in more detail below.…”
Section: White Butterflies (Pieris Brassicae and P Rapae)mentioning
confidence: 92%
“…Other studied glucosinolates were sinigrin, which was slightly active, and glucoiberin, which was completely inactive as a stimulant (Renwick et al, 1992). Another investigation involving oviposition bioassays between cabbage (B. oleracea) leaves and P. brassicae also identified glucobrassicin as the oviposition stimulant (Van Loon et al, 1992). Moreover, Traynier and Truscott (1991) showed that solutions of glucobrassicin purified from foliage and sinigrin elicited oviposition by the cabbage butterfly, P. rapae, at threshold concentrations as low as 10 −6 M while at higher concentrations, glucobrassicin elicited a faster oviposition rate and a stronger visual response to the substrate through associative learning.…”
Section: White Butterflies (Pieris Brassicae and P Rapae)mentioning
confidence: 99%
“…Several specialist insects have developed counteradaptations to circumvent the toxic effects of glucosinolates and their hydrolysis products (Müller et al 2001;Alibadi et al 2002;Ratzka et al 2002;Wittstock et al 2004;Agerbirk et al 2006;Vergara et al 2006;Wheat et al 2007). Moreover, glucosinolates and isothiocyanates often serve as attractants or oviposition and feeding stimulants for these insects (Van Loon et al 1992;Wittstock et al 2003;Miles et al 2005;Schoonhoven et al 2005;Renwick et al 2006;Barth and Jander 2006;Smallegange et al 2007). Still, several studies have shown negative correlations between the glucosinolate content of the diet and the larval performance of herbivorous insects specialized on Brassicaceae (Mewis et al 2005(Mewis et al , 2006Gols et al 2007Gols et al , 2008Kim and Jander 2007).…”
Section: Introductionmentioning
confidence: 99%